2014
DOI: 10.3923/ijomes.2015.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Species Diversity and Community Assemblage of Planktonic Rotifers from Vembanad Estuary-Kerala, India

Abstract: Among the zooplankton, Rotifera comprise an integral part of the food chain and are important link between nanoplankton and carnivorous zooplankton. The diversity of rotifers is indicative of the ecological factors of the water body as they respond more quickly to environmental changes and appear as sensitive indicators of changes of water quality. In this context, species diversity of planktonic rotifers and its community assemblage in Vembanad backwater (Ramsar site) has been carried out from March 2012 to F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
1
0
2
Order By: Relevance
“…Rajagopal et al (2010) supports this finding from three different ponds of Tamilnadu and reported that DO showed a negative correlation with zooplankton abundance. A negative association of DO with rotifer density and diversity has also been reported by Cleetus et al (2015). Esparcia et al (1989) reported that for a short period some rotifers can tolerate anaerobic or near anaerobic conditions even though most rotifers require oxygen concentration above 1.5 mg/l.…”
Section: Canonical Correspondence Analysissupporting
confidence: 57%
See 1 more Smart Citation
“…Rajagopal et al (2010) supports this finding from three different ponds of Tamilnadu and reported that DO showed a negative correlation with zooplankton abundance. A negative association of DO with rotifer density and diversity has also been reported by Cleetus et al (2015). Esparcia et al (1989) reported that for a short period some rotifers can tolerate anaerobic or near anaerobic conditions even though most rotifers require oxygen concentration above 1.5 mg/l.…”
Section: Canonical Correspondence Analysissupporting
confidence: 57%
“…Galkovskaja (1987) stated that, if other factors not limiting, rotifers can reproduce over a wide range of temperatures. Cleetus et al (2015) reported that rotifer density has a significant positive association with nitrate and phosphate and a combination of variables like phosphate, conductivity, salinity, and the temperature was best in determining the diversity and distribution of the rotifer population. All these environmental factors act collectively to determine species abundance and distribution of periphytic rotifers.…”
Section: Canonical Correspondence Analysismentioning
confidence: 99%
“…Este lago, si bien comparte algunas características con el lago Dalcar (reducida transparencia y presencia de peces), se diferencia por su mayor extensión y su salinidad más elevada. La composición taxonómica del zooplancton de Dalcar estuvo dominada por los rotíferos, organismos que constituyen un importante enlace entre el nanoplancton y el zooplancton carnívoro (Retina et al, 2015) y que son capaces de modificar la trama trófica microbiana (Fermani et al, 2013). El dominio de la riqueza de los rotíferos es un rasgo típico de lagos de elevado nivel trófico (Lodi et al, 2011;Sarma et al, 2016) como es Dalcar y es una situación similar a la encontrada en los lagos pampeanos mencionados más arriba, en la laguna de Chascomús (Diovisalvi et al, 2010) y en el eutrófico lago del parque General Belgrano, en el sur de la ciudad de Santa Fe (José de Paggi & Paggi, 1976).…”
Section: Veranounclassified
“…En todos los casos mencionados, al igual que en el lago Dalcar, entre los rotíferos predominaron especies de los géneros Brachionus, Keratella y Lecane, cuyas especies son consideradas indicadoras de eutrofia (Ferdous & Muktadir, 2009;Perbiche-Neves et al, 2013;Sarma et al, 2016;Azma-Hanim & Anis-Amalina, 2016). Además de éstas, otras especies encontradas en Dalcar son indicadores de eutrofia elevada, tales como P. dolichoptera o Filinia longiseta (Čeirāns, 2007;García Chicote, 2015;Retina et al, 2015;Azma-Hanim & Anis-Amalina, 2016).…”
Section: Veranounclassified